Assessing knowledge, attitude and practice on breastfeeding, immunization, and oral care among mothers in Lebanese primary health care centers - El Maaz, Farah (2020)
The prevalence of oral diseases, out breaks in preventable communicable diseases, and reduced breastfeeding rates in both developed and developing countries are major public health problems. Previous literature tackled knowledge, attitude, and practice (K A P) on breastfeeding, immunization, and oral health showing lots of discrepancies. Therefore, findings from studies showed that these public health problems can be resolved if educational interventions are implemented in all of the three child care practices. The objective of this study examines K, A, P on breastfeeding, immunization, and oral health in Lebanese Primary healthcare centers (PHCC) while examining 2 exposure groups; a group that received education and a group that didn’t. This cross sectional study targeted mothers in 4 Lebanese PHC centers during June and November 2019. A multicomponent questionnaire was administered to a convenience sample of participants (N = 1,172). Chi square tests were conducted between exposed and non-exposed groups to education. Factors associated with breastfeeding practice were investigated using multiple logistic regression analysis. The results of the study showed that participants had good immunization practice, yet average knowledge, attitude, and practice in oral health and breastfeeding. The provision of education, having good breastfeeding knowledge indicators, nationality as well as one attitude indicator showed associations with breastfeeding practice. At the end of this study, misconceptions were revealed, as well as low attitude, and reduced practice towards oral health and breastfeeding in mothers attending educational sessions in PHCC. The findings suggest a platform for new community based interventions aiming to enhance breastfeeding rates and reduce dental problems.